Reference of Religious Education Among the Panyabungan Community: An Analysis of the Selection of Tahfidz Schools and the Challenges Faced - Nur, Kholidah; Kasman; Wulandari, Martina Ayu; Hidayati, Zulfa Rahmat (Universitas Muhammadiyah Jember, 2025)
Changing values and priorities in urban societies affect interest and preference for religious education, with many Tahfidz schools becoming an increasingly popular option in response to changing social, cultural, and economic dynamics. The purpose of this study is to look at the preferences of parents of urban communities in choosing schools for their children in terms of social life and the challenges they face. This research is a qualitative research, which uses a sociology approach and a historical approach as an approach to explore the phenomenon that affects the interests and preferences of parents in choosing a school for their children. The results of this study show that parents choose tahfidz schools to increase their children's religiosity, hope for blessings, and rewards of the Qur'an. Other factors such as excellent programs, facilities, and education costs, also influence their decision. The challenges that parents face are time limitations, costs, children's social adjustment, and psychological challenges.